CpG Oligonucleotides Protect Mice From Alphavirus Encephalitis: Role of NK Cells, Interferons, and TNF - Manangeeswaran, Mohanraj; Lewkowicz, Aaron P.; Israely, Tomer; Ireland, Derek D.C.; Verthelyi, Daniela (Frontiers in Immunology, 2020)
Arboviruses including alphavirus are responsible for most emerging infectious diseases worldwide. Recent outbreaks of chikungunya virus serve as a stark reminder to their pathogenic potential. There are no vaccines or therapeutics currently available to contain alphavirus outbreaks. In this study we evaluated the effect of immunomodulatory CpG ODN on the clinical progression of neurotropic Sindbis virus infection. Neonatal C57Bl-6 mice challenged with Sindbis virus AR339 (25 PFU Subcutaneous) infect the neurons in the CNS leading to the development of ataxia, seizures, paralysis and death. We show that systemic administration of CpG ODN modulates the cytokine and chemokine gene expression levels in the CNS and ultimately protects neonatal mice from lethal neurotropic infection. The protection conferred by CpG ODN is controlled by innate immune response and T and B cells were dispensable. Further, protection required Type I, Type II interferons, and TNF as well as functional NK cells, but did not involve iNOS. This study confirms that administration of innate immune modulators can be used as a strategy to boost host innate immune responses and protect against neurotropic viruses reducing their pathogenic footprint.